2016
DOI: 10.1002/dep2.16
|View full text |Cite
|
Sign up to set email alerts
|

Microbial sedimentary imprint on the deep Dead Sea sediment

Abstract: A study of an International Continental Drilling Program core recovered from the middle of the modern Dead Sea has identified microbial traces within this subsurface hypersaline environment. A comparison with an active microbial mat exhibiting similar evaporative processes characterized iron-sulphur mineralization and exopolymeric substances resulting from microbial activity. Exopolymeric substances were identified in the drilled sediment but unlike other hypersaline environments, it appears that they have a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 74 publications
(142 reference statements)
0
20
0
Order By: Relevance
“…These minerals form as products of two reactants that form during early diagenetic anoxic microbial processes: (1) reactive iron (Fe 2+ )-which is a product of microbial iron (Fe 3+ ) reduction and (2) sulfide (S 2− )-which is a product of MSR. Bishop et al (2013) and Thomas et al (2016) suggested that the transformation from monosulfide to pyrite in Dead Sea sediments requires addition of S°. For microbial iron and sulfate reduction to occur, an adequate supply of labile organic matter, iron (Fe 3+ ), and sulfate are required.…”
Section: Greigite Formation In the Dead Seamentioning
confidence: 99%
“…These minerals form as products of two reactants that form during early diagenetic anoxic microbial processes: (1) reactive iron (Fe 2+ )-which is a product of microbial iron (Fe 3+ ) reduction and (2) sulfide (S 2− )-which is a product of MSR. Bishop et al (2013) and Thomas et al (2016) suggested that the transformation from monosulfide to pyrite in Dead Sea sediments requires addition of S°. For microbial iron and sulfate reduction to occur, an adequate supply of labile organic matter, iron (Fe 3+ ), and sulfate are required.…”
Section: Greigite Formation In the Dead Seamentioning
confidence: 99%
“…This could be a result of inclination shallowing, post depositional magnetization, and smoothing of the sedimentary data. As the Holocene Dead Sea sediments are dominated by authigenic greigite (Ron et al, 2006;Frank et al, 2007b;Thomas et al, 2016;Ebert et al, 2018) a complicated magnetic acquisition mechanism is expected. Thus, differences between the archaeomagnetic and the sedimentary data are likely.…”
Section: Comparison With Sedimentary Datamentioning
confidence: 99%
“…Torfstein et al, 2005). It is also the case for magnetic minerals such as greigite or titanomagnetite (Ebert et al, 2018;Thomas et al, 2016). The microorganisms responsible for this sulfate reduction however remain unknown.…”
Section: Introductionmentioning
confidence: 99%